The Articulated Nutritional Program and child malnutrition in the Huánuco Region, Peru - Amancio, Adriana (2024)
Objective. To determine the relationship between the Articulated Nutritional Program (PAN, by its Spanish acronym) and chronic malnutrition in children under 5 years old in the Panao Health Micro Network, Pachitea Province, Huánuco Region (Peru), for the period 2018-2021. Methods: A correlational study with a non-experimental design was conducted. Secondary data from DIRESA-Huánuco and the Friendly Consultation web portal of the Ministry of Economy and Finance were used to estimate Pearson's correlation coefficient. Results: A negative relationship was found between PAN and chronic child malnutrition in the Panao district, with a Pearson correlation coeffcient value of -0.74. Additionally, a negative relationship was found between chronic child malnutrition and the dimensions of PAN: management of PAN goods and services (-0.47), budget allocation (-0.66), and PAN budget execution (-0.70). Conclusions: There is a relationship between PAN and chronic malnutrition in children under 5 years old in the Panao Health Micro Network for the period 2018-2021.